INTRODUCTORY MYCOLOGY - D.P. Tripathi; D.P. Tripathi (Ludhiana Kalyani, 2006)
This book embodies 27 chapters, covering all the important subject sub deciplines of mycology.
Mycology Physiology of Fungi Classification of Fungi
Keywords: Mycology, Physiology of Fungi, Classification of Fungi